2021
DOI: 10.1111/apel.12313
|View full text |Cite
|
Sign up to set email alerts
|

Trade, technology, and the labour market: impacts on wage inequality within countries

Abstract: This paper focuses on the widening wage inequality between skilled and unskilled workers within countries and discusses whether trade and technology have contributed to this trend. The paper develops an analytical framework for wage inequality that traces the determinants and their relative roles in wage inequality in different stages of the development of trade theory, especially those considering new evidence after 2011. We find that technology plays a key role in the rise of wage inequality in most countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 108 publications
1
1
0
1
Order By: Relevance
“…This leads to the inverse movement between technology innovation and labor pricing. The position of this study confirms previous authors' (Walwei, 2016;Gries & Nuade, 2018;Wang et al, 2021) positions that technology advancement promotes inequality in labor relations. Despite the variation in study population, environment and in the methodological approach of this study from the previous studies, the result from this study is in line with earlier findings.…”
Section: Conclusion and Recommendationsupporting
confidence: 90%
See 1 more Smart Citation
“…This leads to the inverse movement between technology innovation and labor pricing. The position of this study confirms previous authors' (Walwei, 2016;Gries & Nuade, 2018;Wang et al, 2021) positions that technology advancement promotes inequality in labor relations. Despite the variation in study population, environment and in the methodological approach of this study from the previous studies, the result from this study is in line with earlier findings.…”
Section: Conclusion and Recommendationsupporting
confidence: 90%
“…They revealed that there is a need to build data for such study in the future. Wang et al (2021) focused on trade and technology roles in reducing wage inequalities among some selected countries. A qualitative research design was used to design a way of measuring wage inequality.…”
Section: Theoretical Review Internal Labor Market Theorymentioning
confidence: 99%
“…Teknologi berkembang secara cepat dan signifikan (Daniel 2020), Sehingga Negara harus bisa adaptasi secara cepat termasuk aspek pendidikan (Verma et al, 2021;Takahashi et al, 2020). Kolaborasi antara bidang pendidikan dengan teknologi adalah komponen yang harus dilakukan (Wang, Findlay, and Thangavelu 2021).…”
Section: Pendahuluanunclassified